Faktor-Faktor Non-Performing Financing (NPF) di Bank Umum Syariah Indonesia - Alvira ‘Aina A’yun, Khofidlotur Rofi’ah, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
The bank's task is as an intermediary institution that is funding and lending. OJK Data shows that each year financing in Sharia banks continues to increase. Therefore sharia banking should prevent the minimum financing to occur and be obliged to know what the factors of the NPF are in order to maintain banking health. The purpose of this research is to know the NPF factors in Indonesia's Sharia bank. The research method used in this research is to use quantitative research with a double linear regression approach. The data used in this study was a monthly data series from the year 2014-2018. The variables used in this study are NPF as variable dependent and CAR, FDR, inflation, SBIS, BOPO as independent variables. The result in the study was the CAR and FDR impactful negative and significant to the NPF, inflation and SBIS impact negative and insignificant, while BOPO influential positive and significant.